Malaria Vector Control and the Electronic Malaria Surveillance Information System (E-SISMAL) in Bangka Barat Regency Indonesia - Asmiani Asmiani; Yuanita Windusari; Hamzah Hasyim (Universitas Airlangga, 2021)
Introduction: Until the end of 2020, West Bangka Regency was the only one that has not been certified for malaria elimination, so that it has an impact on achieving malaria elimination at the provincial level of Bangka Belitung. The West Bangka Regency's Electronic Malaria Surveillance Information System (E-SISMAL) showed eight indigenous malaria cases and no malaria vector control reports in 2020. The indigenous cases in West Bangka Regency have prevented malaria elimination. This study aims to evaluate malaria vector control to help eliminate malaria. Methods: This research was a qualitative evaluation study with selected informants. E-SISMAL in West Bangka Regency was studied and was analysed with Nvivo 12 Plus for Windows. The variables studied were context, input, process, and product. Focus groups, in-depth interviews, participatory observation, and photovoice were used to collect data. Results and Discussion: The area's topography, miner's behaviour, lack of manual vector reporting, and extensive ex-mining pits were discussed. Each evaluation variable was constrained by the process (supporting data collection and sub-variables) and product (data coverage of malaria vector control in E-SISMAL). Conclusion: It can be concluded that each evaluation variable constrains malaria vector control in West Bangka Regency.